Reactive oxygen species rescue regeneration after silencing the MAPK–ERK signaling pathway in Schmidtea mediterranea - V. Jaenen (Nature Portfolio, 2021)
Abstract Despite extensive research on molecular pathways controlling the process of regeneration in model organisms, little is known about the actual initiation signals necessary to induce regeneration. Recently, the activation of ERK signaling has been shown to be required to initiate regeneration in planarians. However, how ERK signaling is activated remains unknown. Reactive Oxygen Species (ROS) are well-known early signals necessary for regeneration in several models, including planarians. Still, the probable interplay between ROS and MAPK/ERK has not yet been described. Here, by interfering with major mediators (ROS, EGFR and MAPK/ERK), we were able to identify wound-induced ROS, and specifically H2O2, as upstream cues in the activation of regeneration. Our data demonstrate new relationships between regeneration-related ROS production and MAPK/ERK activation at the earliest regeneration stages, as well as the involvement of the EGFR-signaling pathway. Our results suggest that (1) ROS and/or H2O2 have the potential to rescue regeneration after MEK-inhibition, either by H2O2-treatment or light therapy, (2) ROS and/or H2O2 are required for the activation of MAPK/ERK signaling pathway, (3) the EGFR pathway can mediate ROS production and the activation of MAPK/ERK during planarian regeneration.